Indian society - Dube, S.C. (New Delhi, 2005)
This book is addressed to young readers who want to know something about the historical roots, ideological foundations, and social organization of Indian society. The last chapter discusses the major trends of change. For its data and interpretations, the book draws upon such diverse sources as history, Indology, anthropology, and sociology. The insights provided by these disciplines are, I believe, necessary to illuminate the social realities of India.
Keywords: Societies